PERANCANGAN APLIKASI PEMBELIAN DAN PRODUKSI MINYAK KELAPA SAWIT PADA PT. PALMA ABADI JAMBI BERBASIS WEB - Hendri Hendri; M. Riza Pahlevi; Hartoyo Hartoyo (Jurnal Processor, 2020)
Palma Abadi Jambi is one of company which has been located in Jambi which the processes of the dissemination of information and processing the data for purchase palm oil like still use book help. So that problems occur that is spreading information takes a very long time of branch offices to headquarters, often mistakes recording and calculation total money for data buying and selling, the absence of a system that can calculating the cost of oil every day, and preparing reports that takes time relatively long. Because of that, this research have purpose to give solution to that happening problems with offer a application of purchasing and production palm oil with using PHP programming language and MySQL database where writer make development system with waterfall method and using model approach system unified model language with use case diagram, activity diagram, class diagram and flowchart diagram. The new system produce outputs that can showing location data, employees data, product data, purchase data, customers data, selling data, cash data, cost data and reports that can be printed with purpose of can tell us a quick and easier information to the management of data the purchasing and production palm oil.